155/157Gd areal density: A model for design and fabrication of Gd2O3/316L novel neutron shielding composites. (June 2020) - Wan, Shipeng; Wang, Wenxian; Chen, Hongsheng; Zhou, Jun; Zhang, Yuyang; Liu, Ruifeng; Feng, Ruyi
Abstract: The Monte Carlo N-Particle Code were used to design a novel Gd2 O3 /316L stainless steel neutron shielding composites (Gd2 O3 /316L NSCs). And the constitutive equation between the 155/157 Gd areal density and the neutron shielding rate was established by MCNP. When the areal density of 155/157 Gd is larger than 0.01 g/cm 2, the thermal neutron shielding rate of the composites reaches 99%. The NSCs with three weight fractions (1.5 wt%, 2.5 wt%, and 4.5 wt% Gd2 O3 ) were successfully fabricated by spark plasma sintering. And Gd2 O3 particles evenly distributed in 316L matrix. The main phases of the composite are austenite (γ-Fe) and Gd2 O3, and in addition Fe2 Gd and Gd2 Ni17 are present at the interface of Gd2 O3 and 316L matrix particles. The debonding of the Gd2 O3 particles is the main cause of material fracture. Highlights: 155/157 Gd areal density was used to evaluate the neutron shielding efficiency of composites containing Gd. The constitutive relationship between neutron shielding rate and 155/157 Gd areal density was established. Suitable Gd2 O3 contents for the fabrication of Gd2 O3 /316L NSCs were given in the present study. The mechanical properties of Gd2 O3 /316L NSCs were studied.